THE EFFECT OF TAXES, EARNINGS PER SHARE, AND SALES GROWTH ON STOCK PRICES IN THE COVID-19 PANDEMIC (EMPIRICAL STUDY OF HEALTH AND PHARMACEUTICAL SECTOR LISTED IN THE JAKARTA STOCK EXCHANGE 2016-2020) - Cahyani Tunggal Sari; Mamik Suharti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine and empirically prove the effect of tax rates, earnings per share and sales growth on stock prices in health and pharmaceutical sector companies listed on the Jakarta Stock Exchange for the 2018-2020 period. This research uses quantitative research that is associative. The population in this study is the health and pharmaceutical sector companies listed on the Jakarta Stock Exchange in 2018-2020, as many as 17 companies. Sampling was done by using a purposive sampling technique, total 16 companies for three years or 48 data were obtained. Data analysis in this study was carried out using multiple linear regression analysis. The results showed that partially earning per share had a positive and significant effect on stock prices, while tax rates and sales growth had no significant effect on stock prices. Simultaneously tax rates, earnings per share and sales growth have a significant effect on stock prices.